2014
DOI: 10.4314/ahs.v13i4.4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and audiometric features of presbycusis in Nigerians

Abstract: Background: Presbycusis is the most common sensory impairment associated with ageing and it presents with variability of symptoms. Physicians need to recognize early clinical and audiometric signs of presbycusis in order to render adequate and quality care to patients and reduce associated morbidities. Objective: To characterize the clinical modes of presentation and the typical audiometric tracings among patients with presbycusis. Methods: This descriptive, prospective hospital-based study was conducted in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 25 publications
2
22
0
6
Order By: Relevance
“…In patients with diabetes, two possible mechanisms have been proposed, microangiopathic lesions in the inner ear leading to cochlear hearing disorder or primary neuropathy of the cochlear nerve resulting in a retrocochlear hearing loss. [10] Unlike our patient's sudden clinical presentation of SNHL, diabetes associated hearing loss is usually progressive, bilateral, sensorineural of gradual onset. [13] Moreover, the patient's glycemic levels were controlled.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In patients with diabetes, two possible mechanisms have been proposed, microangiopathic lesions in the inner ear leading to cochlear hearing disorder or primary neuropathy of the cochlear nerve resulting in a retrocochlear hearing loss. [10] Unlike our patient's sudden clinical presentation of SNHL, diabetes associated hearing loss is usually progressive, bilateral, sensorineural of gradual onset. [13] Moreover, the patient's glycemic levels were controlled.…”
Section: Discussionmentioning
confidence: 79%
“…[9] While diclofenac is found to be associated with hearing loss, other insults to the cochlea from diabetes mellitus, hypertension and aging may also contribute to the decline in hearing experienced by the patient. Presbycusis or age-related hearing loss, which occurs due to degenerative changes in the cochlear hair cells and neurons in the cochlear nerve and its central auditory connections, [10] is bilaterally symmetrical, usually insidious in onset, gradually progressing and starts from middle age and continues into older years. [4,10] However, our patient had no history of hearing loss previously and the current presentation was a sudden onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found bilateral tinnitus in more than 50% of individuals with presbycusis 26,28 . In this study, tinnitus was the symptom most frequently reported by the participants in both groups, with prevalences similar to the values reported by the abovementioned studies.…”
mentioning
confidence: 99%
“…It is considered to be the sensory deficiency most commonly associated with aging, with a prevalence of up to 35% among individuals aged 60 to 70 years old 26 . In this study, more than 70% of the sample exhibited mild-to-moderate hearing loss (Table 4), with a mild downward sloping configuration in both groups (Table 3).…”
mentioning
confidence: 99%